2009
DOI: 10.1007/s10535-009-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a dispersed repeated DNA element in the Zamia genome

Abstract: Occurrence and genomic organization of dispersed elements containing ZpS1 satellite repeats have been investigated in a wide representation of species of the old plant genus Zamia (Zamiaceae, Cycadales). In Z. paucijuga, the ZpS1 repeat is organized as long satellite DNA arrays and as short arrays inserted into AT-rich dispersed elements. A comparative study by Southern analysis shows that these unusual dispersed elements containing the ZpS1 repeat are present with different organizations in all investigated Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…complex in Mexico (Vovides & Olivares, 1996; Stevenson, Moretti & Gaudio, 1998) show similar DNA sequence patterns [note that Z. loddigesii is now recognized as Z. prasina , for example, by Vovides & Olivares (1996)], whereas the banding pattern in Z. neurophyllidia D.W.Stev. differs from that of the other closely related basal Central American taxa (Cafasso et al ., 2009). Repeated sequences create multiple sequence homologies on chromosomes, which may cause alternative pairing arrangements and may, in turn, promote chromosomal fission.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…complex in Mexico (Vovides & Olivares, 1996; Stevenson, Moretti & Gaudio, 1998) show similar DNA sequence patterns [note that Z. loddigesii is now recognized as Z. prasina , for example, by Vovides & Olivares (1996)], whereas the banding pattern in Z. neurophyllidia D.W.Stev. differs from that of the other closely related basal Central American taxa (Cafasso et al ., 2009). Repeated sequences create multiple sequence homologies on chromosomes, which may cause alternative pairing arrangements and may, in turn, promote chromosomal fission.…”
Section: Discussionmentioning
confidence: 57%
“…There are only six cycad records in the C ‐value database (Ohri & Khoshoo, 1986; Leitch et al ., 2001; Murray, Leitch & Bennett, 2004). However, Cafasso et al . (2009) reported that all Zamia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are reports on nuclear DNA content determined using Feulgen microdensitometry in only four species of Cycadales (Ohri & Khoshoo 1986) but these deviate strongly from the results presented here. Cafasso et al. (2009) reported relative genome sizes in 32 Zamia species, all of which had an identical genome size (but see this article).…”
Section: Introductionmentioning
confidence: 99%